THE EXPRESSION OF FLORAL ORGAN IDENTITY GENES, TgAP2, TgAP3, TgPI, TgSEP AND TgAG, ON STAGE OF FLORAL ORGAN OF TEAK (Tectona grandis L. f) - Mustari, Eri
Teak (Tectona grandis L.f.) is a timber producing plant of high economic value, due to its strength and durability properties. The flower formation of generative phase is the problem in timber production in teak because it can inhibit the timber development. Inhibition of the flowers formation can extend the vegetative period so can extend the period of wood formation. Genetic engineering in flowering regulation is one of the effort to delay flower formation. The study of expression of flowering genes is the starting point to engineer the phase of flower formation. Information on the regulation of flowering genes in teak is still limited. However, the regulation of flowering genes in Arabidopsis has been extensively studied, including into flowering time genes, meristem identity genes and floral organ identity genes. Floral organ identity genes in Arabidopsis are AP2, AP3, SEP, PI and AG. Floral organ identity genes such as AP2 induce sepals, AP3 and PI induces on petals and stamens, SEP induces on petals, stamens and carpels, while AG induces on stamen and carpel. Previous research has analyzed the transcriptome profiles in total RNA sequences of vegetative and generative buds in teak, and have identified are TgLFY, TgAP1 and TgTFL genes on floral meristem identity genes and TgAG in floral organ identity genes, while are TgAP2, TgAP3, TgPI, TgSEP genes have not known their role in the stage of floral organ of teak. The objective of the study was to study the development of floral organ in the flowering stage, evaluate the expression of genes and clustering TgAP2, TgAP3, TgPI, TgSEP and TgAG genes on stages of floral organ. Morphological and histological observations on apical vegetative buds, apical floral buds, 2thlateral floral buds, 4thlateral floral buds and floral buds by paraffin method. Evaluating the genes expression of TgAP2, TgAP3, TgPI, TgSEP and TgAG on stages of floral organs beginning to determinate genes from transcriptome, primer design, histology analysis, RNA isolation, cDNA synthesis, gene expression using QRT PCR using 18S Ribosomal RNA as gene reference. The clustering of genes from the genes expression of TgAP2, TgAP3, TgPI, TgSEP and TgAG on stages of floral organs with cluster analysis using Ward's Algorithm method, Pearson correlation analysis using GenEx software, database confirmation of process and biological functions on Arabidopsis using genemania software g: profiler, and confirmation with the flowering genes regulation model in Arabidopsis based on Blazquez. The results of histologic observation on the apical vegetative buds of primordia by apical buds are as follows, in apical floral buds, 2th lateral floral buds and 4th lateral floral buds of flower branches, each of iv which has three branching. Floral buds have branches that have three branches of inflorescence, and each branch of sepals of primordia, petals of primordia, stamens of primordia and carpels of primordia. The results of the expression analysis of genes on apical vegetative buds showed that TgAP2, TgAP3, TgPI, TgSEP and TgAG are expressed at different levels of gene expression on stage of floral organs. In apical floral buds, 2th lateral floral buds, 4th lateral floral buds, showed that TgAP2, TgAP3, TgPI, TgSEP and TgAG are expressed at different levels of gene expression on the development of branches. In floral buds, showed that TgAP2, TgAP3, TgPI, TgSEP and TgAG are expressed with different levels of gene expression to sepals of primordia, petals of primordia, stamens of primordia and carpels of primordia. The clustering of genes on the expression showed that TgAP2, TgAP3, TgPI, TgSEP and TgAG on apical vegetative buds, apical floral buds, 2th lateral floral buds and 4th lateral floral buds are predicted to the branches of inflorescence, while the clustering of genes on the expression in floral buds are predicted to sepals of primordial expressed by TgAP2 and TgAP3, petals of primordia expressed by TgAP2, TgAP3, TgPI and TgSEP, stamens of primordia expressed by TgPI, TgSEP and TgAG, carpels of primordia expressed by TgSEP and TgAG.